ANALYSIS OF THE ERUPTION PROCESS OF MOUNT MERAPI - Inelia Febriska; Dzalika HR Diyanti PA; Nurul Hasanah (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to analyze the basic processes of Mount Merapi's eruption through a simple simulation using readily available materials, such as baking soda, vinegar, and liquid soap. This simulation is conducted in the form of a lab experiment to help students understand how gas pressure in the "earth's bowels" can cause a volcanic eruption. In the experiment, the reaction between baking soda and vinegar produces carbon dioxide gas, which creates pressure that pushes the liquid mixture outward, resembling lava. Observations show that the eruption began 2.21 seconds after the ingredients were mixed, the jet reached a height of 2.8 meters, and lasted for about 4 minutes. This simulation provides a simple yet effective illustration of the eruption mechanism and can be a fun and relevant contextual learning tool. Through this activity, students not only learn scientific concepts but also practice observation and critical thinking skills. This lab also fosters awareness of the importance of disaster preparedness. The simplicity of the tools and materials makes this experiment easy to perform in any learning environment. The results obtained are quite representative in describing the process of pressure and gas release that occurs in volcanic eruptions. Therefore, this activity is highly recommended as an interactive learning medium in science subjects.